Loss of NFBD1/MDC1 disrupts homologous recombination repair and sensitizes nasopharyngeal carcinoma cells to PARP inhibitors - Wang, Zhihai (J Biomed Sci, 2019)
BACKGROUND: Nasopharyngeal carcinoma (NPC), a highly invasive tumor, exhibits a distinctive racial and geographic distribution. As options of agents for effective combination chemoradiotherapy for advanced NPC are limited, novel therapeutic approaches are desperately needed. Here the potential of silencing NFBD1 in combination with PARP inhibition as a novel therapeutic strategy for NPC was investigated. METHODS: To investigate the function of NFBD1, we created NFBD1-depleted NPC cell lines via lentivirus mediated shRNA, and the colony formation, MTS assay, comet assay and apoptosis analysis were used to evaluate the sensitivity of NFBD1 knockdown on PARP inhibition. The signaling change was assessed by western blot, Immunofluorescence and flow cytometry. Furthermore, Xenografts model was used to evaluate the role of silencing NFBD1 in combination with PARP inhibition. RESULTS: We find that silencing NFBD1 in combination with PARP inhibition significantly inhibits the cell proliferation and cell cycle checkpoint activity, and increases the apoptosis and DNA damage. Mechanistic studies reveal that NFBD1 loss blocks olaparib-induced homologous recombination repair by decreasing the formation of BRCA1, BRCA2 and RAD51 foci. Furthermore, the xenograft tumor model demonstrated significantly increases sensitivity towards PARP inhibition under NFBD1 deficiency. CONCLUSIONS: We show that NFBD1 depletion may possess sensitizing effects of PARP inhibitor, and consequently offers novel therapeutic options for a significant subset of patients.